Influence of Fan Behaviour on the Self-Esteem of Amateur Athletes in Kwara State, Nigeria - Adebayo Babatunde Samson; Ibraheem Musa Oluwatoyin (Universitas Majalengka, 2021)
Since the inception of organized sports, there have been fans or spectators cheering for their favorite athletes and teams in order to increase their confidence and improve their overall performance. This study examined the influence of fan behaviour on the self-esteem of amateur athletes in Kwara State. The variables investigated are fans’ perception, discrimination, violent reactions, and feelings of disappointment. Descriptive research design of survey method was adopted for the study. The population for the study was amateur athletes from four sports (Football, Basketball, Volleyball, and Handball). Purposive and sample technique was used for the study. The sample for the study consists of 140 amateur athletes in Kwara State. The research instrument for this study was questionnaire developed by the researcher which was used for data collection. Frequency and percentage was used to analyze the demographic data of respondents while the hypotheses were tested using inferential statistic of Chi-square at 0.05 alpha level. The findings of the study revealed that; fans perception of athletes as a failure, discrimination, violent reactions, and feelings of disappointment influenced the self-esteem of amateur athletes. Based on the findings, the study recommends that stakeholders such as media, sports council and relevant agencies of government should conduct enlightenment programmes on management and control of fan behaviour in Kwara State.